World-Centred Peace Education: Toward a Framework for Socio-Eco Peace in Times of Systemic Crisis - Gittins, Phill (In Factis Pax: Journal of Peace Education and Social Justice, 2025)
This article develops a novel framework for world-centred peace education in response to today’s interconnected social and ecological crises. It critiques anthropocentric models and the War System, arguing for a paradigm shift that centres relationality and the interdependence of people and planet. The framework is grounded in the concept of socio-eco peace—a vision of mutual flourishing—and integrates a guiding purpose, a relational worldview, theoretical influences, and five interrelated domains: inner, outer, context, pluralism, and process. These domains support peace education that is holistic, inclusive, and responsive to place, time, and community. The article explores how the framework can inform the design, facilitation, and evaluation of peace education across diverse settings, and concludes with implications for theory, policy, practice, and future research.